A rare case of osteonecrosis of patella following quadriceps distractive lengthening for neglected non-union patella - Vaibhav Sahu; Nitesh Jain (Journal of Orthopaedic Reports)
Neglected patella fracture non-unions are extremely rare and contraction of the quadriceps femoris muscle makes it immensely difficult to operate non-union patella after a long time. A case of mid patella fracture which was neglected for 18 months is presented. The patient had a history of trauma to his right knee and presented to us with difficulty in walking due to malfunctioning of extensor mechanism. He also had a 10 cm distance between two fragments of patella. The quadriceps femoris muscle was lengthened by using Joshi's external stabilization system (JESS) and finally, when fragments came closer to each other, they were fixed with 2 k-wires and tension band wiring. At 2-year follow-up the patient was ambulating independently but came with complaints of pain and discharge from the suture site due to infection. Plain radiographs were taken and suggested of deformed and sclerosed patella. Magnetic resonance imaging scan confirmed the diagnosis of osteonecrosis of patella. Osteonecrosis of the patella has been rarely described after trauma and the peculiarity in this case is that osteonecrosis occurs not after the 18 months of trauma but 22 months after the fixation of fractured patella.